Trastuzumab administration in patients with metastatic breast cancer: experience of a large university breast center = Verträglichkeit und klinische Praxis der Trastuzumab-Langzeitbehandlung von Patientinnen mitmetastasiertem Mammakarzinom : Erfahrungen aus einem großen universitären Brustzentrum - Hartkopf, Andreas; Brendel, M. H.; Wallwiener, Markus; Taran, F.-A.; Brucker, S.; Grischke, E.-M. (Geburtshilfe und Frauenheilkunde, 2014)
Background: Administered either alone or in combination with various cytostatic, endocrine or targeted therapies, trastuzumab significantly improves the prognosis of patients with HER2-positive breast cancer. As trastuzumab is effective across multiple lines of therapy in the metastatic setting (treatment beyond progression: TBP), it is often administered over a long period of time. The aim of this study was to evaluate the tolerability and clinical practice of long-term trastuzumab administration (> 1 year) in metastatic breast cancer patients treated in a large university breast center. Methods: Metastatic breast cancer patients who received at least 18 cycles of trastuzumab administered every three weeks at the University Gynecological Hospital of Tuebingen between 1999 and 2012 were included in this retrospective study. Typical combination drugs, side effects, and the impact of administration on left ventricular ejection fraction (LVEF) were investigated. Results: 72 patients were eligible for inclusion in the study. The mean number of administrations was 50.14 (SD: 27.51). In 53 patients the principle of TBP was followed across an average of 2.4 therapy lines. Classic cardiac risk factors were present at the beginning of trastuzumab treatment in 34 patients (47 %). Seven patients (10 %) experienced a decrease in LVEF during treatment, 9 patients (13 %) had hypersensitivity reactions. Treatment was discontinued in two patients due to side effects (1 × progressive LVEF decrease, 1 × intolerance). Summary: The administration of trastuzumab across multiple lines of therapy was generally tolerated well. Cardiac risk factors were not a limiting factor. If regular cardiac monitoring is done, trastuzumab appears not only to improve survival but also helps preserve the quality of life of patients with HER2-positive metastatic breast cancer.
Gesehen am 14.08.2020